Ribosomal protein L32 contributes to the growth, antibiotic resistance and virulence of Glaesserella parasuis - Chen, Qiaodan; Yu, Bin; Su, Fei; Ye, Shiyi; Xu, Lihua; Yuan, Xiufang; Wu, Shumin; Zhang, Hui; Li, Junxing (Frontiers in Veterinary Science, 2024)
Glaesserella parasuis is the pathogen that causes Glässer’s disease in pigs, which is characterized by fibrinous polyserositis, arthritis and meningitis. Research on ribosomal protein L32 in microorganisms has mainly focused on regulating gene transcription and translation, but its effect on bacterial virulence is unclear. The role of L32 gene in G. parasuis is not clear, and in order to study the function of L32 gene, a suicide plasmid-mediated natural transformation method was used to construct a L32 gene deletion mutant. We found that although L32 was shown to be non-essential for cell proliferation, the growth curve of ΔL32 is clearly different compared with that of ZJ1208. ΔL32 produced more outer membrane vesicles (OMVs) with a variety of irregular shapes, but produced similar biofilm to the parental strain. ΔL32 is more sensitive to osmotic pressure, oxidation pressure and heat shock stress. Meanwhile, ΔL32 is significantly more susceptible to antimicrobials such as spectinomycin, apramycin, sulfafurazole, but not to other antibiotics used in this study. In the mouse challenge experiment, the mortality of mice infected with the mutant strain decreased by 40% compared to those infected with the wild-type strain, indicating that L32 is a virulence-associated factor which contributes to bacterial fitness in host environments. The above results show that L32 is important for the growth, stress resistance and virulence of G. parasuis, and this study also confirms for the first time that L32 plays an important role in antibiotic resistance against aminoglycosides and sulfonamides.